Polysaccharide microarray technology for the detection of Burkholderia pseudomallei and Burkholderia mallei antibodies - Parthasarathy, Narayanan (Diagn Microbiol Infect Dis, 2006)
A polysaccharide microarray platform was prepared by immobilizing Burkholderia pseudomallei and Burkholderia mallei polysaccharides. This polysaccharide array was tested with success for detecting B. pseudomallei and B. mallei serum (human and animal) antibodies. The advantages of this microarray technology over the current serodiagnosis of the above bacterial infections were discussed.